2008
DOI: 10.1002/cmdc.200800108
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular uptake and inhibitory activity of aromatic fluorinated amino acids in human breast cancer cells

Abstract: Nonproteinogenic amino acids that either occur naturally or are synthesized chemically are becoming important tools in modern drug discovery. In this context, fluorinated amino acids have great potential in the development of novel pharmaceuticals and drugs. To assess whether different fluorinated aromatic amino acid analogues of phenylalanine, tyrosine, and tryptophan are potentially interesting as therapeutic drugs, we examined their cytostatic and cytotoxic effects on the growth of the human breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
(44 reference statements)
1
18
0
1
Order By: Relevance
“…Indeed, Wang and co-workers observed roughly 9 mM intracellular dansylalanine upon esterification of the amino acid [62]. Giese et al recently demonstrated that fluorinated tryptophan is actively taken up into mammalian cells to an intracellular concentration exceeding the extracelluar by 70-fold [63]. A comparable accumulation could elevate the intracellular Bpa concentration above 5 mM when the cells are supplemented with 1 mM in the medium, as in our experiments.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, Wang and co-workers observed roughly 9 mM intracellular dansylalanine upon esterification of the amino acid [62]. Giese et al recently demonstrated that fluorinated tryptophan is actively taken up into mammalian cells to an intracellular concentration exceeding the extracelluar by 70-fold [63]. A comparable accumulation could elevate the intracellular Bpa concentration above 5 mM when the cells are supplemented with 1 mM in the medium, as in our experiments.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, future work is needed to develop PylRS variants that will efficiently acylate Mycoplasma cell-permeable ncAAs, under conditions that lead to high levels of these AAs in the cell. [26] Engineering AARS variants with high catalytic efficiencies for ncAAs is particularly important, because many currently available orthogonal pairs are inefficient compared with natural AARSs. [27] …”
Section: Discussionmentioning
confidence: 99%
“…Since the elevated uptake of glucose and increased glycolitic activity of cancer cells has been first reported by Otto Warburg,9 it has been shown that in addition to glucose many molecules (amino acids, vitamins) are accumulated in cancer cells 10–12. The accumulation of these substances by cancer cells is utilized in positron emission tomography,13 and targeting strategies has been started to emerge on the basis of amino acid and vitamin accumulation 14, 15. In recent years it became increasingly clear that there are a significant number of common signaling pathways regulating both cellular metabolism and cell proliferation 16.…”
Section: Introductionmentioning
confidence: 99%